2016
DOI: 10.1039/c6cc02632j
|View full text |Cite
|
Sign up to set email alerts
|

Sweet supramolecular elastomers from α,ω-(β-cyclodextrin terminated) PDMS

Abstract: Azido β-cyclodextrins were attached to propiolate-functionalized polydimethylsiloxanes by metal-free click chemistry. The obtained telechelic copolymers spontaneously produced elastomeric gums. Demixing and supramolecular associations are the driving forces for the construction of these strongly associated (but reversible) physical networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Rambarran et al. showed that, following the PR reaction, Huisgen or azide/alkyne click reactions could be used to create silicone/PEG (or cyclodextrin) surfactants (Figure B), elastomers (Figure C), copolymers or adhesives . The most important orthogonal reaction in silicone systems is platinum‐catalyzed hydrosilylation (see below) …”
Section: Piers–rubinsztajn (Pr) Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rambarran et al. showed that, following the PR reaction, Huisgen or azide/alkyne click reactions could be used to create silicone/PEG (or cyclodextrin) surfactants (Figure B), elastomers (Figure C), copolymers or adhesives . The most important orthogonal reaction in silicone systems is platinum‐catalyzed hydrosilylation (see below) …”
Section: Piers–rubinsztajn (Pr) Reactionmentioning
confidence: 99%
“…For example, polymers of fluorocarbons and silicones were shown to result from sequential PR reactions and then thermolysis to facilitate 2 + 2c ycloadditions with perfluoroalkenes to give linear or crosslinked polymers ( Figure 9A). [47] Rambarran et al showed that, following the PR reaction,H uisgen or azide/alkyne click reactions could be used to create silicone/PEG (or cyclodextrin) surfactants (Figure 9B), [48] elastomers ( Figure 9C), [49] copolymers [50] or adhesives. [51] The most important orthogonal reaction in silicone systemsisp latinum-catalyzed hydrosilylation (see below).…”
Section: Aroh and Arosimentioning
confidence: 99%
“…Over the last years, important advances have been made in the field of smart materials, especially for intrinsic self-healing polymer materials, which exploit dynamic bonds, typically generated by supramolecular chemistry approaches, to create self-assembling networks. 1,2 Noncovalent cross-linked systems via supramolecular interactions, such as π-π stacking, [3][4][5] ionic interactions (eg, ionomers), [6][7][8] metal-ligand associations [9][10][11][12] and, in most cases, hydrogen-bonding interactions, [13][14][15][16][17][18][19] have been developed and characterized for this purpose. In some cases, the approach relies on the modification of polymers with functional groups that can interact with each other through explicit strong or weak associations, resulting in the formation of a phase different from the bulk polymer.…”
Section: Introductionmentioning
confidence: 99%
“…N ‐Methyl‐2‐sulfanylacetamide ( 4 ) was also selected in order to introduce a relatively hydrophilic group able to provide strong hydrogen bonding and to impart solubility to the corresponding grafted polysiloxane in polar solvents, such as DMF or DMSO. Actually, such polysiloxanes soluble in DMF or DMSO are interesting for the preparation of carbohydrate grafted polysiloxanes (‘glycosilicones’), since they would enable the direct grafting of unprotected carbohydrate moieties in monophasic conditions …”
Section: Introductionmentioning
confidence: 99%
“…Actually, such polysiloxanes soluble in DMF or DMSO are interesting for the preparation of carbohydrate grafted polysiloxanes ('glycosilicones'), since they would enable the direct grafting of unprotected carbohydrate moieties in monophasic conditions. [56][57][58] Concerning the gold nanoparticles, the wavelength of the Surface Plasmon resonance (SPR) absorption band is affected by many factors. [59,60] It is mainly affected by the particle shape, [61] dimensions and aggregation.…”
Section: Introductionmentioning
confidence: 99%